Exploring Psychological Drivers in Dynamic Pricing and Consumer Decision Making - Niemeier, Christian; Pospisil, Richard (Manunggal Halim Jaya, 2025)
This research aims to explore psychological aspects of consumers’ decision-making process from the perspective of dynamic pricing strategies in e-commerce systems. As online retail continues to grow, exploring pricing algorithms, UX, and consumer behaviors becomes vital to businesses and researchers Which leads to research questions. How do consumers perceive and respond to dynamic pricing; how perceived UX affects consumers’ interactions with dynamic pricing; what is the effect of ethical considerations on consumers’ trust and engagement. The results show that there exists a complex relation between pricing methods , customer experience components and psychological factors. Studies found that range of price dynamicity and the equity of the actions determines buyers’ attitudes towards DPs’ changes. From the study, better UX design development of easy-to-understand interfaces and value propositions has higher acceptance by consumers. The issue of data protection and price policies occupy a significant portion of consumer credibility and brand sustainment. The discussion adds value on how psychological processes trigger consumers responses to dynamic prices. This study acts as a handbook for ethical and efficient pricing methodologies that fit the budget firm, keeping the consumer's content. Furthermore, it forms the basis for future studies of the dynamics of online retail and consumer behaviour in e-commerce.